Measurement of the top quark mass using events with a single reconstructed top quark in pp collisions at √s = 13 TeV; Journal of High Energy Physics; Vol. 2021, iss. 12 - Tumasyan A. R.; Adam W. Wolfgang; Andrejkovic J. W. Aleksandr Dmitrievich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen